2016
DOI: 10.1007/s10068-016-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactobacillus plantarum Lb41, an isolate from kimchi and its application as a probiotic in cottage cheese

Abstract: Lb41 was determined probiotic properties and applied to cottage cheese. Lb41 showed high viability (>80%) in artificial gastric (pH 2.5, 0.3% pepsin for 3 h) and bile (0.3% oxgall for 24 h) acids, and adhered strongly to HT-29 cells (7.5% adhesion). It did not produce β-glucuronidase and was resistant to several antibiotics. Lb41 did not inhibit proliferation of normal MRC-5 cells, but showed antiproliferative effects on AGS, HT-29, and LoVo cells, based on 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…The cells were maintained in Dulbecco's modified Eagle's medium (DMEM; Hyclone) with 10% (v/v) FBS and 1% (v/v) P/S at 37°C in a 5% CO 2 incubator. The amount of NO produced and MTT assay were evaluated using the method described by Jeon et al [20] and Lee et al [16], respectively.…”
Section: Cytotoxicity and Nitric Oxide (No) Production Ability Of Labmentioning
confidence: 99%
“…The cells were maintained in Dulbecco's modified Eagle's medium (DMEM; Hyclone) with 10% (v/v) FBS and 1% (v/v) P/S at 37°C in a 5% CO 2 incubator. The amount of NO produced and MTT assay were evaluated using the method described by Jeon et al [20] and Lee et al [16], respectively.…”
Section: Cytotoxicity and Nitric Oxide (No) Production Ability Of Labmentioning
confidence: 99%
“…Resistance of Bacillus strains to artificial gastric juice and bile salts was determined following protocol published by Jeon et al [14]. Resistance of Bacillus to artificial gastric juice was assessed using TSB containing 0.3% (w/v) pepsin (Sigma-Aldrich, St. Louis, MO, USA) adjusted to pH 2.5 with 0.1 M HCl and incubated for 3 h with shaking (150 rpm).…”
Section: Resistance To Artificial Gastric Juice and Bile Saltsmentioning
confidence: 99%
“…Many studies have reported lactic acid bacteria as probiotics isolated from kimchi. However, few research studies have reported probiotic Bacillus strains isolated from kimchi [13][14][15]. Many Bacillus species have been isolated from fermented soybean food and applied in industrial products as probiotics for many years [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…It also improves consumer’s satisfaction by obtaining healthier and ready-to-use foods [ 27 ]. There have been several studies on the enrichment of fermented milk products with probiotics, such as enrichment of Cheddar [ 28 ], Manchego [ 29 ], Cottage [ 30 ], Turkish Beyaz [ 31 ], Argentinean [ 32 ], and white cheese [ 33 ].…”
Section: Discussionmentioning
confidence: 99%